Why do critical audit matters lack teeth? Insights from auditors’ implementation experiences - Griffith, Emily E.; Rousseau, Linette M.; Zehms, Karla M. (Review of Accounting Studies, 2026)
The PCAOB adopted critical audit matters (CAMs) to meet public demand for informative audit disclosure, but stakeholders are concerned this goal has not been achieved. We explore this disconnect via interviews with 30 highly experienced auditors. We find that audit firms expended considerable resources to implement CAM best practices. However, overwhelming institutional pressure gave rise to informal rules of thumb that prioritize symbolic comfort over substantive change. The first is don’t be an outlier , so auditors defer to the national office to ensure conformity and avoid PCAOB scrutiny. The second is report the “right” number of CAMs by never reporting zero and reporting at least one recurring CAM. The third is avoid surprises by communicating with the client to ensure that CAMs do not contain original information and allowing management to preempt auditor disclosures. Collectively, these rules yield CAMs that comply with PCAOB standards but do not provide new information and instead maintain the status quo.